HUKUMAN EDUKATIF UNTUK ANAK MI/SD - YUBERTI, YUBERTI (Universitas Islam Negeri Raden Intan Lampung, 2014)
Making of punishment which tends to be negative of course very disturbing world of education. Should not the punishment as a method or tool to discipline children can be interpreted more positively? Should not the punishment be educational method that guarantees creativity and intelligence of children so that they can develop properly? Punishment in education is not a form of torture, both physical and spiritual at will we give to the children. Instead, the penalty is an effort we do to restore the child towards a better and motivate them to become a person who is imaginative, creative, and productive.